Effect of Native Gastric Mucus on in vivo Hybridization Therapies Directed at Helicobacter pylori - Rita S. Santos (2015)
Helicobacter pylori infects more than 50% of the worldwide population. It is mostly found deep in the gastric mucus lining of the stomach, being a major cause of peptic ulcers and gastric adenocarcinoma. To face the increasing resistance of H. pylori to antibiotics, antimicrobial nucleic acid mimics are a promising alternative. In particular, locked nucleic acids (LNA)/2'-OMethyl RNA (2'OMe) have shown to specifically target H. pylori, as evidenced by in situ hybridization. The success of in vivo hybridization depends on the ability of these nucleic acids to penetrate the major physical barriers-the highly viscoelastic gastric mucus and the bacterial cell envelope. We found that LNA/2'OMe is capable of diffusing rapidly through native, undiluted, gastric mucus isolated from porcine stomachs, without degradation. Moreover, although LNA/2'OMe hybridization was still successful without permeabilization and fixation of the bacteria, which is normally part of in vitro studies, the ability of LNA/2'OMe to efficiently hybridize with H. pylori was hampered by the presence of mucus. Future research should focus on developing nanocarriers that shield LNA/2'OMe from components in the gastric mucus, while remaining capable of diffusing through the mucus and delivering these nucleic acid mimics directly into the bacteria.